Status of ICT in Teaching and Learning of basic Science in Upper basic School in Anambra East Local Government Area of Anambra State Nigeria - Tobechukwu Ebele Okeke (Indonesian Journal of Innovative Teaching and Learning, 2024)
Background: The integration of Information and Communication Technology (ICT) into education has the potential to enhance teaching and learning, especially in science education. However, the actual status and effectiveness of ICT use in schools remain uncertain in many regions, including Anambra East Local Government Area of Anambra State, Nigeria. Objective: This study aimed to investigate the current status of ICT in the teaching and learning of Basic Science in upper basic schools within Anambra East LGA, identifying both its impacts and the challenges hindering its effective implementation. Method: A descriptive survey design was adopted. The sample consisted of 194 Basic Science teachers selected through simple random sampling from secondary schools in Anambra East. Data were collected using structured questionnaires, interviews, and direct observations. The instruments were validated and tested for reliability. Data analysis employed a 4-point Likert scale, with a mean cut-off point of 2.5 for acceptance. Result: The findings revealed that ICT use enhances student engagement, promotes skill development, and supports personalized learning experiences. However, significant challenges were identified, including inadequate funding, limited teacher training, insufficient practical application time, and poor monitoring and evaluation mechanisms. Conclusion: Despite its potential, the effective integration of ICT in Basic Science teaching is constrained by systemic and infrastructural challenges. Addressing these barriers is essential for maximizing ICT's benefits in education. Contribution: The study provides empirical insight into the current ICT landscape in Basic Science education at the upper basic school level in Anambra East. It highlights areas needing intervention and informs policymakers, educators, and stakeholders on strategic actions to enhance ICT adoption and effectiveness in science teaching.